Local knowledge and attitudes of the young Filipino cisgender sports community on transgender athletes - Jayme, Anya Patricia J. 2000-
Transgender people are now more visible than ever in different fields and sectors of society, including sports. However, visibility does not mean acceptance, and the discourse from the sports community that surrounds the inclusion of trans athletes in sports is not always supportive and can seek to exclude and discriminate against them. This descriptive study aims to investigate the young cis Filipino sports community in relation to trans athletes specifically examining levels of perceived and knowledge and attitudes of acceptance among them. A survey developed for the study was administered to a small sample of young cis Filipinos involved in sports (n = 36). With the use of likert-scale items, they were asked to self-report awareness with concepts relating to trans people and experiences, and their agreement with statements relating to the inclusion of trans athletes in sports. It was found that the participants had high levels of perceived general knowledge but lacked more specific knowledge in the context of trans athletes and sports. Additionally, participants were found to be generally accepting of trans athletes in sports, and supportive of inclusion Responses to open-ended questions in the survey added more nuance to these findings with responses following the themes of interpersonal comfort with trans athletes belief in inclusion, and a focus on trans women vs. fairness. This shows that the discourse surrounding trans athletes and inclusion is present in the Filipino sports community and that research on this issue in a local level has its place in the larger discourse